Effects of Urolithin A supplementation on performance and antioxidant status in academy soccer players during preseason: a pilot randomised controlled trial - Monsalve Acevedo, Andrea; Sanctuary, Colin; Aitken, Robert John; Wilkins, Alex; Harrison, Natasha; Naughton, Mitchell (Frontiers in Nutrition, 2025)
BackgroundPolyphenol-derived compounds, such as Urolithin A (UA), may exert beneficial effects to performance adaptations during periods of high training stress through several pathways including a reduction in an oxidative stress and improved mitochondrial function. At present, the benefits of UA supplementation have been observed predominantly in clinical and preclinical models. This pilot study aimed to investigate the effects of UA supplementation on performance outcomes, antioxidant status, and intervention feasibility and acceptability during a six-week preseason period in academy soccer players.MethodsTwenty male academy soccer players (age: 17.5 ± 1.0 years) were randomly assigned 1:1 to receive 1,000 mg/day of UA or an isocaloric taste-matched placebo which was given post-training over the course of a six-week training intervention in a single-blinded, parallel-group design. The intervention was delivered alongside the team’s preseason training from November to December 2024. Primary outcome was aerobic endurance (Yo-Yo Intermittent Recovery Test Level 1), with secondary outcomes including lower-limb strength and power metrics (Countermovement Jump), maximal sprinting speed, and salivary antioxidant capacity using the RoXsta™ System. Each of the primary and secondary outcomes were assessed pre and post the intervention. Feasibility and acceptability of the intervention along with dietary intake was assessed via individual questionnaire, pre and post intervention, while subjective stress-recovery status was assessed via questionnaire administered weekly over the duration of the intervention. Primary and secondary data were analysed using linear mixed effects models, with group (UA/placebo) × time (pre/post) interactions interpreted using estimated marginal means.ResultsUA supplementation led to significantly greater improvements in Yo-Yo IRT1 performance compared to placebo (Δ = +239 m, 95% CI [20, 454 m], p = 0.048). For secondary outcomes, countermovement jump height also improved in the UA group relative to placebo (Δ = +3.33 cm, [0.88, 5.95 cm], p = 0.020). No group x time differences were observed in sprint speed, jump power, impulse, or eccentric duration, or saliva antioxidant assays. Antioxidant activity declined significantly over time in the placebo group but did not so in the UA group. Feasibility and acceptability questionnaire responses indicated the intervention as it was delivered was rated with high feasibility and acceptability.ConclusionSix weeks of UA supplementation during preseason improved aerobic endurance and some measures of jump performance in elite academy soccer players, while preserving aspects of antioxidant status. Confidence limits on the primary and secondary findings were broad. These findings potentially support UA as a feasible and well-tolerated intervention in athletic populations, warranting further research in larger and well powered confirmatory trials (Clinical Trial No. ACTRN12624000959572).